Application of Mind Mapping Method in Learning to Write Geguritan to Students of Class IX A SMP Negeri 04 Bumiayu Brebes Regency in the Academic Year 2023/2024 - Pitaloka, Zanis; Alfiah, Alfiah; Zaidah, Nuning (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This study aims to describe the results of applying the mind mapping method in learning to write geguritan for students of class IX A at SMP Negeri 04 Bumiayu, Brebes Regency. This is motivated by the continued lack of interest among many students in learning to write geguritan, which is partly due to the limited variety of learning methods used. Therefore, the application of the mind mapping method is needed to facilitate students in participating in learning, so that later students can develop their ideas and creativity, especially when participating in learning to write geguritan. This study used a descriptive quantitative approach while the design in this study was a pre-experimental design in the form of a one-shot study involving only one group without the need for sampling. The data of this study were collected through questionnaires (questionnaires) accompanied by documentation. While the data collection techniques in this study used test and non-test techniques. The results of this study are: 1) in the knowledge aspect competency test, a percentage of 100% or a total of 24 students obtained a complete score above the KKM. From this acquisition, the final average score was 85.58. 2) in the skill aspect competency test also obtained a percentage of 92% or 22 students whose scores had reached above the KKM. From this acquisition, the final average score was 80.25 in the skill aspect. Based on the analysis of the data obtained, learning to write geguritan can provide a considerable influence on learning activities to write geguritan in class IXA SMP Negeri 04 Bumiayu Brebes Regency.